2019
DOI: 10.1186/s12931-019-1103-1
|View full text |Cite
|
Sign up to set email alerts
|

CFTR regulates B cell activation and lymphoid follicle development

Abstract: Background Cystic fibrosis (CF) is an inherited disorder caused by mutations in the CF transmembrane conductance regulator (CFTR) gene that promotes persistent lung infection and inflammation and progressive loss of lung function. Patients with CF have increased lung lymphoid follicles (LFs) and B cell-activating factor of tumor necrosis factor family (BAFF) that regulates B cell survival and maturation. A direct role for CFTR in B cell activation and disease pathogenesis in CF remains unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…The model of chronic Pa lung infection favours the retention of the bacteria in the airways and reproduces some features of the CF lung disease such as strong neutrophilic inflammation and peribronchial lymphoid aggregates [ 47 , 48 ]. Only a slight increased inflammatory score in FVB F508del mice was demonstrated, in contrast with C57BL/6J CFTR-KO mice showing some lymphoid aggregates [ 49 , 50 ]. When compared with the same genetic background, CFTR-KO and F508del mice display the same phenotype and, until now, no diseased lung phenotype related to CFTR misfolding has been observed in F508del mice [51] .…”
Section: Discussionmentioning
confidence: 99%
“…The model of chronic Pa lung infection favours the retention of the bacteria in the airways and reproduces some features of the CF lung disease such as strong neutrophilic inflammation and peribronchial lymphoid aggregates [ 47 , 48 ]. Only a slight increased inflammatory score in FVB F508del mice was demonstrated, in contrast with C57BL/6J CFTR-KO mice showing some lymphoid aggregates [ 49 , 50 ]. When compared with the same genetic background, CFTR-KO and F508del mice display the same phenotype and, until now, no diseased lung phenotype related to CFTR misfolding has been observed in F508del mice [51] .…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune responses, in contrast, are directed against self-antigens and are characterised by the presence of autoreactive T cells and B cell-mediated autoantibodies [ 34 ]. Only a limited number of studies have reported the involvement of adaptive immune cells, such as T and B cells, affected by CFTR mutations in CF pathology [ 36 39 ]. Therefore, this review will explore existing reports in the literature detailing several mechanistic signalling pathways dysregulated in innate immune cells harbouring CFTR mutations.…”
Section: Introduction: An Overview Of Cystic Fibrosismentioning
confidence: 99%
“…Studies in Cftr -/mice suggest that CFTR mutations directly affect B lymphocyte function. Uninfected Cftr -/mice have higher levels of the B cell survival factor, B cell-activating factor (BAFF), a member of TNF cytokine family, as well as an increased number of lung lymphoid follicles compared to control mice (141). Increased levels of BAFF and lymphoid follicles were also observed in CF patients (141).…”
Section: Possible Contribution Of Immune Cells In Progression To Cfrd In Cf Patientsmentioning
confidence: 99%
“…Uninfected Cftr -/mice have higher levels of the B cell survival factor, B cell-activating factor (BAFF), a member of TNF cytokine family, as well as an increased number of lung lymphoid follicles compared to control mice (141). Increased levels of BAFF and lymphoid follicles were also observed in CF patients (141). Moreover, the pancreas of newborn CFTR -/pigs present with a higher proportion of activated B lymphocytes, likely producing antibodies.…”
Section: Possible Contribution Of Immune Cells In Progression To Cfrd In Cf Patientsmentioning
confidence: 99%